Brain injury and offending: the development and field testing of a linkworker intervention - Ramos, Sara D. S. (International journal of offender therapy and comparative criminology, 2018)
Evidence suggests that traumatic brain injury (TBI) is more prevalent amongst offender populations than in the general population, and that it can lead to aggressive behaviour while in custody and impair engagement with offender rehabilitation programmes. The aim of this study was to develop, implement, and evaluate a brain injury Linkworker approach designed to support prisoners who report a significant TBI or multiple mild TBIs. Three clinical case examples are reported to illustrate the conceptual foundations of the approach and to demonstrate the feasibility of the service. Early results showed that engagement with a Linkworker led to effective identification of key areas of intervention and resulted in better integration for prisoners while in custody and in enhancement of the outcomes of offender rehabilitation. These initial findings provide justification for wider implementation and systematic evaluation of the efficacy of this model of service.